Trail of labor versus elective repeat cesarean section: a comparison of morbidity and mortality at tertiary care teaching hospitals in India - Dhillon, Balwan Singh; Chandhiok, Nomita; Rao, M. Vishnu Vardhana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: As cesarean birth rates continue to rise, more women are faced with the choice of planning a vaginal delivery or a repeat cesarean section after a previous cesarean section. The objective of this prospective study was to study the morbidities and mortality of women attempting a trial of labor after cesarean (TOLAC) versus elective repeat cesarean section (El-RCS). Methods: Prospective data was recorded on management practices, associated complications and morbidity & mortality for a period of 8 months on 15664 consecutive cases of previous cesarean section reporting at 30 medical colleges/ teaching hospitals for delivery. Results: A trial of labor was planned in 25.8% (4035) women and 34.5% (5399) women underwent elective repeat cesarean section and rest had emergency repeat cesarean section. Overall maternal morbidity due to any cause was 20.7% among El-RCS as compared to 14.2% in TOLAC which was statistically significant (OR: 1.57, CI: 1.41-1.76, P=0.00). Blood loss of more than 1000ml was around 8.0% among TOLAC where as in El-RCS it was 8.8% (OR: 0.89, CI: 0.77-1.94, p=0.14 not statistically significant). Blood transfusion was given in 3.7% in TOLAC where as in El-RCS it was given in 6.5% (OR: 0.56, CI: 0.45-0.68, p=0.00 highly significant). Complication like dehiscence of scar was similar in both groups. Post-operative complication were seen in 2.8% cases in TOLAC where as in El-RCS it was 5.8% (OR: 0.47, CI: 0.38-0.59, p=0.00 highly significant). Uterine rupture was 0.3% in TOLAC where as in El-RCS it was 0.7% (OR: 0.43, CI: 0.21-0.87, p=0.009 statistically significant). Maternal mortality was reported in 0.2% cases of TOLAC as compared to 0.1% cases in El-RCS (p=0.17) which was not statistically significant. Conclusions: Maternal morbidity was found to be more in elective repeat cesarean section than trial of labor after cesarean section.